2022
DOI: 10.1093/mnras/stac3089
|View full text |Cite
|
Sign up to set email alerts
|

MUSE Analysis of Gas around Galaxies (MAGG) – IV. The gaseous environment of z ∼ 3–4 Ly α emitting galaxies

Abstract: We study the link between galaxies and H i-selected absorption systems at z ∼ 3 − 4 in the MUSE Analysis of Gas around Galaxies (MAGG) survey, an ESO large programme consisting of integral field spectroscopic observations of 28 quasar fields hosting 61 strong absorbers with $\rm N_{\rm HI}\gtrsim 10^{16.5}~\rm cm^{-2}$. We identify 127 Lyα emitting galaxies (LAEs) around the absorbers, corresponding to a detection rate of 82±16 per cent. The luminosity function of these LAEs is ≈5 times higher in normalization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 149 publications
0
21
0
1
Order By: Relevance
“…The authors also interpret the absorber as located within a gaseous filament possibly accreting onto one of the nearby galaxies. The latest MAGG results (the characterized environments of 61 absorbers) in Lofthouse et al (2023) similarly show that LLSs at these high redshifts are either located in regions close to galaxies (3-4 R vir ) or likely in filaments of the IGM. Although it is outside of the LLS column density range, we also note the detection of an SLLS (…”
Section: Comparison To High-z Surveysmentioning
confidence: 77%
“…The authors also interpret the absorber as located within a gaseous filament possibly accreting onto one of the nearby galaxies. The latest MAGG results (the characterized environments of 61 absorbers) in Lofthouse et al (2023) similarly show that LLSs at these high redshifts are either located in regions close to galaxies (3-4 R vir ) or likely in filaments of the IGM. Although it is outside of the LLS column density range, we also note the detection of an SLLS (…”
Section: Comparison To High-z Surveysmentioning
confidence: 77%
“…These observational challenges have made the study of quasar fields particularly insightful because the quasar light is selectively absorbed by the IGM and CGM as it travels to the observer, which reveals the gas in and around galaxies that reside in field, cluster, and group environments (Bechtold 2001;Khare 2013;Chen et al 2020;Dutta et al 2020Dutta et al , 2021Lofthouse et al 2023). In the past, these studies were limited by the requirement that sources needed to be preselected for targeting with long-slit or fixed aperture multi-object spectroscopy, which can bias the galaxy sample.…”
Section: Scientific Motivationmentioning
confidence: 99%
“…Morphology, inclination, azimuthal angle with respect to the major axis of a galaxy, and environment of galaxies also influence the quantity of gas that the quasar sight line intercepts; therefore the connection between them and the properties of absorption lines are widely investigated (e.g., Kacprzak et al 2007;Bordoloi et al 2011;Kacprzak et al 2011;Cunnama et al 2014; Barnes et al 2014;Tumlinson et al 2017;Lan & Mo 2018;Ho et al 2020;Lee et al 2021). In the last few years, blind searches for galaxies associated with absorbers also revealed that the absorber's properties are related to the gravitational interactions in the group populations, galaxy's outflows, intergalactic medium accretions, star formation rates, and gas distributions within a galaxy group (e.g., Fossati et al 2019;Nielsen et al 2020;Bielby et al 2020;Dutta et al 2020;Muzahid et al 2021;Nielsen & Kacprzak 2022;Lofthouse et al 2023). In addition, one absorber might be associated with multiple galaxies within a group as well (e.g., Bielby et al 2020;Lofthouse et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, blind searches for galaxies associated with absorbers also revealed that the absorber's properties are related to the gravitational interactions in the group populations, galaxy's outflows, intergalactic medium accretions, star formation rates, and gas distributions within a galaxy group (e.g., Fossati et al 2019;Nielsen et al 2020;Bielby et al 2020;Dutta et al 2020;Muzahid et al 2021;Nielsen & Kacprzak 2022;Lofthouse et al 2023). In addition, one absorber might be associated with multiple galaxies within a group as well (e.g., Bielby et al 2020;Lofthouse et al 2023).…”
Section: Introductionmentioning
confidence: 99%